USE OF ECOENZYMES IN MINIMIZING THE USE OF CHEMICAL PRODUCTS AND ANALYSIS RESULTS OF THE PRODUCTS PRODUCED: PEMANFAATAN EKOENZIM DALAM MEMINIMALISIR PENGGUNAAN PRODUK KIMIA SERTA HASIL ANALYSIS TERHADAP PRODUK YANG DIHASILKAN - Novi Mailidarni; Jauhari; Juliawati (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2024)
Ecoenzymes are products produced from the hardening process of fruitpeels and molasses (brown sugar) for 3 months in the form of liquid liquid.Ecoenzymes have many benefits, ranging from cleaning fluids, insecticides,natural fertilizers to health. In this study we used 7 fruit skins, namely orange,pineapple, kates, melon, watermelon, apple and pear peels. The researchmethod analyzes the water content and pH value. Through this research, it was found that the ecoenzymes from the 7 fruit peels had very good ecoenzyme criteria to be used for a mixture of disinfectants and skin irritation resulting in a pH of 4.0, a water content of 83% and an organoleptic color and aroma of 4.25 (very like it).